Nonlocal Metric Dimension of Windmill Graph - Lathifah, Fithri Annisatun (Program Studi Matematika, Universitas Nusa Cendana, 2025)
Let G = (V (G), E(G)) be a simple and connected graph. The distance between two vertices u and vin G, is the length of a shortest path from u to v, denoted by d(u, v). Suppose S = s1, s2, ...sk is anordered subset of vertices of G, then the metric representation of a vertex u ∈ V (G) with respect to S,denoted by r(u|S), is the k−vector (d(u, s1), d(u, s2), ..., d(u, sk)). If every two nonadjacent vertices ofG have distinct metric representations with respect to S, then the set S is called a nonlocal resolvingset for G. A nonlocal resolving set with minimum cardinality is called a nonlocal metric basis. Thenonlocal metric dimension of G is the cardinality of the nonlocal metric basis of G and is denoted bynldim(G). In this paper, we obtained nonlocal metric dimension of windmill graph.